2010
DOI: 10.1162/rest_a_00038
|View full text |Cite
|
Sign up to set email alerts
|

School Quality and Residential Property Values: Evidence from Vancouver Rezoning

Abstract: This study utilizes changes in the catchment areas of public schools in Vancouver, British Columbia, to measure the residential price capitalization of school quality. Specifications that employ repeat sales methods to control for time-invariant neighborhood effects and disaggregated price indexes to capture time-varying neighborhood price appreciation reveal significant effects of secondary school performance on residential prices. However, when we add controls for long-run price trends in rezoned areas, only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
80
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 15 publications
9
80
0
Order By: Relevance
“…In other words, living environment has a significant influence on housing prices. This inference is consistent with the findings of Ries and Somerville (2010). In conclusion, differences between the housing prices of new towns and old urban areas are attributed to the distinct living environments in the two regions.…”
Section: Research Datasupporting
confidence: 92%
See 1 more Smart Citation
“…In other words, living environment has a significant influence on housing prices. This inference is consistent with the findings of Ries and Somerville (2010). In conclusion, differences between the housing prices of new towns and old urban areas are attributed to the distinct living environments in the two regions.…”
Section: Research Datasupporting
confidence: 92%
“…Equipped with six schools and six parks, the TUSD is a university special zone featuring a low building coverage ratio, high greenness coverage, underground cables and telecommunications equipment, and an environment tuned for living. Previous studies have found that factors such as school quality (Ries and Somerville, 2010) and park size (Song and Knaap, 2004;Hoshino and Kuriyama, 2010) have significant influences on housing prices. In the case of implementing revitalization projects to rundown areas (to the south of the TUSD is Old Sanxia and to the north is Old Shulin), these projects fail inevitably because of the lack of public participation and explicit policy support (Leinberger, 2005).…”
Section: Hypothesismentioning
confidence: 99%
“…In Bogart and Cromwell (2000), a neighborhood is like a catchment area because each neighborhood is associated with an elementary school. Ries and Somerville (2010) use the definition by the British Columbia Assessment Authority in Vancouver, Canada. 7 Although it is sometimes called the boundary discontinuity approach, BFE is different from the traditional regression discontinuity approach adopted by Cellini et al (2010).…”
Section: School Vs Neighborhood Effectsmentioning
confidence: 99%
“…Second, the inclusion of fixed effects typically reduces variation arising from unobservables, thereby increasing the relative importance of any measurement error in the data (Clapp et al, 2008). In fact, studies find that school quality measures tend to show a significant component of random variation across years (Kane and Staiger, 2002a;Ries and Somerville, 2010). This measurement error in test scores may bias downwards the effect of school quality on house values in a fixed effects model (Brasington and Haurin 2006).…”
Section: School Vs Neighborhood Effectsmentioning
confidence: 99%
See 1 more Smart Citation